Relationship between helicobacter pylori infection and nonsteroidal anti-inflammatory drug-induced gastroduodenal mucosal injury - Sait BAĞCI; Haşim ÇAKIRBAY; Murat DEMİRİZ and Mustafa GÜLŞEN and Mehmet KARALAR and Oktay ARPACIOĞLU and Ahmet ALPER (Turkish Journal of Gastroenterology, 2020)
-